The CORRELATION BETWEEN EMOTIONAL INTELLIGENCE AND READING COMPREHENSION ACHIEVEMENT OF THE ELEVENTH GRADE STUDENTS - herawati unmura (STKIP PGRI Lubuklinggau, 2018)
Theory of emotional intelligence has been proven to contribute to the teaching and learning process, and increase students’ achievement. This research was aimed to investigate whether or not there was correlation betweem emotional intelligence and reading comprehension achievement of the eleventh grade students of SMAN 2 Kota Lubuklinggau. Two hundred and ninety four students participated in this research. Emotional intelligence questionnaire and reading comprehension test were used as the instruments. Analyses by Pearson Product-Moment Correlation revealed that there was a significant correlation between emotional intelligence and reading comprehension achievement with r-obtained (.155) and p (.008). Among the four aspects of emotional intelligence, only emotional management correlated significantly with reading comprehension achievement. Furthermore, regression analyses showed that emotional management had 2.5% contribution in predicting students’ reading comprehension.